Factor Influencing Brand Loyalty of Asian Paints User in Kathmandu Valley - Baidhya, Sapana (Patan Prospective Journal, 2022)
Purpose - It is tremendous competitive world, the companies have to keep up the long term relationship with the customers and essential to span of attention to the customers. Nowadays most of the customers purchase the products consideration of brand rather than inspecting the products. Brand loyalty is extent of the faithfulness on belief of customers to a particular brand, expressed through respect purchase. The main purpose of this study is to explore the factor influencing brand Asian Paints user in Kathmandu valley. Methodology – Descriptive and quantitative research design have been used for the study. Primary data has been collected through questionnaires using probability proportional sampling developed in five Likert scale for measuring factor influencing brand loyalty for Asian Paints user in Kathmandu valley Mean and Standard deviation have been used as tools for measurement. Findings –The empirical finding of this study variables found that the consumers have high brand royal due satisfaction and experience of Asian paints among the five variables based on average mean Score. Trust leads the repurchase of Asian paints is most consideration factor of the customers among different individual evaluation. Customers can quickly recall the logo of Asian Brand, is the least consideration and insufficient sector, this item is more consideration by Asian paints. Policy Implications – This research can be implicated for success and capture of market share of any product due to brand loyalty by improving the insufficient sectors which enhance the betterment of customer’s trust and faithfulness.